2019
DOI: 10.1021/acs.inorgchem.8b03399
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Metal/Chalcogen Composition in Copper(I)–Chalcogenide Clusters with Cyclic (Alkyl)(amino)carbene Ligands

Abstract: A series of phosphorescent homo-and heterometallic copper(I)−chalcogenide clusters stabilized by cyclic (alkyl)(amino)carbene ligands [Cu 4 M 4 (μ 3 -E) 4 (CAAC Cy ) 4 ] (M = Cu, Ag, Au; E = S, Se) has been synthesized by the reaction of the new copper(I) trimethylsilylchalcogenolate compounds [(CAAC Cy )CuESiMe 3 ] with ligand-supported group 11 acetates. The clusters are emissive at 77 K in solution and the solid state, with emission colors that depend on the metal/chalcogen composition. Electronic structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 83 publications
1
15
0
Order By: Relevance
“…John F. Corrigan and co-workers reported the synthesis (Scheme 1b) and the structure of a series of small copper(I)−chalcogenide cluster [Cu4M4(μ3-E)4(CAAC Cy )4] (M=Cu, Au, Ag; E=S, Se) stabilized by cyclic (alkyl)(amino)carbene ligands. 158 Regardless of the heteroatom or the chalcogen present in the cluster, they were isostructural and isomorphous, crystalizing in the monoclinic C2/c space group. The copper atoms in the Cu4 core have nearly planar arrangement and form a square.…”
Section: Sulphur-bridged Cuncsmentioning
confidence: 99%
See 1 more Smart Citation
“…John F. Corrigan and co-workers reported the synthesis (Scheme 1b) and the structure of a series of small copper(I)−chalcogenide cluster [Cu4M4(μ3-E)4(CAAC Cy )4] (M=Cu, Au, Ag; E=S, Se) stabilized by cyclic (alkyl)(amino)carbene ligands. 158 Regardless of the heteroatom or the chalcogen present in the cluster, they were isostructural and isomorphous, crystalizing in the monoclinic C2/c space group. The copper atoms in the Cu4 core have nearly planar arrangement and form a square.…”
Section: Sulphur-bridged Cuncsmentioning
confidence: 99%
“…152 On the same note, [Cu4M4(μ3-E)4(CAAC Cy )4] (M = Cu, Ag, Au; E = S, Se) clusters reported by John F. Corrigan and co-workers, have the same "butterfly"-geometries regardless of the heteroatom doping and bridging chalcogen. 158 [Cu12Se6(dppo)4] cluster 165 is isostructural to its sulphidebridged analog, 164 yet a slight variation in bond lengths is observed. The same group also reported Te-bridged Cu4(μ4-Te)(μ4-η 2 -Te2)(μ-dppf)2] and [Cu12(μ5-Te)(μ8-η 2 -Te2)(μ-dppf)4] clusters containing telluride and ditelluride ligands in their CuTe architectures (Scheme 2a).…”
Section: Selenium/tellurium-bridged Cuncsmentioning
confidence: 99%
“…reported that the introduction of Ag I into the octacopper(I) sulfide cluster, [Cu 8 (μ 3 ‐S) 4 (CAAC Cy ) 4 ], gives isostructural [Cu 4 Ag 4 (μ 3 ‐S) 4 (CAAC Cy ) 4 ] with the emission energy changing from ca. 560 nm to 540 nm [7b] . In this system, the emission quantum yield of the heterometallic Cu 4 Ag 4 cluster is half that of the homometallic Cu 8 S 4 cluster, and thus, the enhancement of emission has not been achieved by heterometallation.…”
Section: Introductionmentioning
confidence: 87%
“…Corrigan et al. synthesized a series of phosphorescent homo‐ and heterometallic copper(I)‐chalcogenide clusters stabilized by cAAC‐ligands [Cu 4 M 4 (μ 3 ‐E) 4 (cAAC Cy ) 4 ] (M=Cu, Ag, Au; E=S, Se) ( 233 ) by the reaction of the new copper(I) trimethylsilylchalcogenolate compounds [(cAAC Cy )CuESiMe 3 ] with ligand‐supported group 11 acetates [303] …”
Section: Areas Of Caac Chemistrymentioning
confidence: 99%